Trust, security and public interest: Striking the balance: A review of previous literature on public attitudes towards the sharing, linking and use of administrative data for research - Waind, Elizabeth (International Journal of Population Data Science, 2020)
This literature review explores previous work in relation to the UK public’s attitudes towards the sharing, linking and use of administrative data for research. It finds the public is broadly supportive of administrative data research if three core conditions are met: public interest, privacy and security, and trust and transparency. None of these three conditions is sufficient in isolation; rather, the literature shows public support is underpinned by a minimum standard of all three. However, it also shows that in certain cases where the standard of one condition is very high – for example, public interest – this could mean that of another – for example, privacy and security – may, if necessary, be lower. An appropriate balance must be struck, and the proposed benefit must outweigh the potential risk. Broad, conditional support for the use of administrative data in research has not only been found consistently, but has also been held over time, with data collection for the 16 studies included spanning more than a decade from 2006-2018. It is therefore, at this time, appropriate to move beyond widescale, general consultation on the use of administrative data for research and build upon existing knowledge by delving into specific areas of research. The purpose of such an approach would not be to consult on whether research using administrative data should be done – as has been the focus of previous literature – but rather to guide how, why and when it is done. Nevertheless, it is important to continue to monitor and respond to any changes to public attitudes and adapt approaches if necessary.